Tomato and mini-cucumber tolerance to photoperiodic injury involves photorespiration and the engagement of nighttime cyclic electron flow from dynamic LEDs - Marie, Telesphore R. J. G.; Leonardos, Evangelos Demos; Rana, Naheed; Grodzinski, Bernard (Frontiers in Plant Science, 2024)
Controlled environment agriculture (CEA) is critical for achieving year-round food security in many regions of the world. CEA is a resource intensive endeavour, with lighting consuming a large fraction of the energy. To lessen the burden on the grid and save costs, an extended photoperiod strategy can take advantage of off-peak time-of-day options from utility suppliers. However, extending the photoperiod limits crop production morphologically and physiologically if pushed too long. Here, we present a continuous light dynamic LED strategy (involving changes in spectra, intensity, and timing) that overcomes these limitations for tomato, a photoperiodic injury sensitive species that has been extensively studied, by providing circadian rhythm entraining cues. Constrained by the need for circadian entrainment, canopy architecture can be tuned by minor variations of the same dynamic LED strategy, and we highlight "dynamic 1" as the optimal choice. Dynamic 1 exceeded total biomass and plant height, without compromising leaf mass per area, compared to a control 16hr photoperiod. A high throughput protocol using the MultispeQ instrument was able to discern subtle acclimation differences between two variations of the dynamic LED treatment. Dynamic 1 engaged the useful type I response that adjusts ATP:NADPH ratio. Whereas dynamic 2 engaged the stressful type II response that uses energy dissipative non-photochemical quenching (NPQ). Interestingly, diurnal MultispeQ measurements point to the importance of cyclic electron flow at subjective nighttime that may partially explain why dynamic LED strategies mitigate photoperiodic injury. A central discovery came from a leaf-level gas exchange and fluorescence protocol that found dynamic 1 had a significantly higher level of photorespiration than control. In parallel, photoperiodic injury tolerant mini-cucumber underwent identical treatments which revealed photorespiration as a common photostasis mechanism employed for continuous light tolerance in both C3 species. Surprisingly, preliminary data on a fully tolerant tomato genotype grown under continuous light upregulates photorespiration to the same amount as mini-cucumber. To our knowledge, the relationship between photoperiodic injury and photorespiration is poorly understood. We discuss the ontology of photoperiodic injury involving photorespiration, triose phosphate utilization, peroxisomal H2O2catalase balance, and a circadian external coincidence model of sensitivity that initiates programmed cell death.